2021
DOI: 10.1097/01.naj.0000737292.96068.18
|View full text |Cite
|
Sign up to set email alerts
|

A Call to the CMS: Mandate Adequate Professional Nurse Staffing in Nursing Homes

Abstract: Editor's note: This article is by 22 nursing gerontology experts who are all advocates of nursing home reform. They are listed at the end of this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…The positive yet short term effect suggested that nursing home staff are willing to learn but reinforcement is needed to sustain the learning effect, such as having skilled staff nurses to provide in-house training (Kolanowski et al, 2021) and providing booster sessions and case discussion (Pulsford et al, 2011). These strategies for continuing education among nursing-home staff highlight the importance of organizational support (Chan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The positive yet short term effect suggested that nursing home staff are willing to learn but reinforcement is needed to sustain the learning effect, such as having skilled staff nurses to provide in-house training (Kolanowski et al, 2021) and providing booster sessions and case discussion (Pulsford et al, 2011). These strategies for continuing education among nursing-home staff highlight the importance of organizational support (Chan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…42 Experts in NH care quality have become increasingly concerned about the lack of 24-hour-a-day, 7-day-a-week RN presence. 13 , 15 In addition, Rantz and colleagues 43 have joined other voices in pointing out the critical need for NH APRNs. Key advantages of APRNs working on-site in NHs are that not only can they evaluate and treat ill residents, but they also have the skills to coach staff in their understanding of clinical assessment, early illness identification, and management of ill residents.…”
Section: Changing Quality Of Care In Nursing Homesmentioning
confidence: 99%
“…12 Most NHs follow the minimum federal regulations for staffing. 13 These regulations require 1 RN on duty 8 consecutive hours per day, 7 days per week, and 1 RN on call when a licensed practical nurse (LPN) is on duty. [14][15][16] The national average for licensed nursing staff hours per resident is 1 hour 44 minutes per day (RN = 46 minutes; LPN/licensed vocational nurse [LVN] = 58 minutes).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…23 The COVID-19 pandemic highlighted the need for the 24-h presence of registered nurses in nursing homes to meet the psychosocial and physical needs of the older adults. 24 …”
Section: Introduction and Definitionmentioning
confidence: 99%